Early and continuing grandparental care and middle school students' educational and mental health outcomes in China. Issue 2 (6th July 2022) - Hong, Yanbi; Zeng, Diyang
Abstract: Several recent studies have examined the relationship between grandparents and grandchildren, but few have examined the effects of early and continuing grandparental care on children's development in China. Using data from the China Education Panel Survey, this study examines the effects of early and continuing care, in which grandparents serve as primary caregivers on middle school students' educational (measured by academic performance and cognitive scores) and mental health (depression score) outcomes. Using multilevel analyses and robustness tests, the results show that for urban and rural students, students cared for by their grandparents showed no disadvantages in their educational outcomes. For rural students who received grandparental care in early childhood or adolescence academically outperformed those who received only parental care. Urban and rural students who received only grandparental care in early childhood and adolescence show worse mental health outcomes. These results challenge the prevailing belief that grandparent caregiving can harm grandchildren's school preparation and cognitive abilities.